The Impact of Globalization and Scientific and Technological Developments on Family Behavior and the Dynamics of Islamic Family Law - Nurafni; Khairunas Rajab; Arisman; Rudy Asrianto (Universitas Negeri Jakarta, 2026)
Globalization and the advancement of science and technology have brought significant changes to Muslim family life, affecting both social behavior and the practice of Islamic family law. These transformations have generated tensions between established legal norms and evolving social realities. This study aims to analyze the dual impact of globalization and technological development on the transformation of Muslim family behavior and the dynamics of Islamic family law in responding to such changes. Employing a qualitative socio-legal approach with a case study design, the research was conducted in several metropolitan cities with predominantly Muslim populations. Data were collected through a literature review and analyzed using an interactive analysis model to examine the gap between social realities (das Sein) and normative legal frameworks (das Sollen). The findings reveal a shift in family values toward individualism, a redefinition of gender roles within households, and an increase in digitally mediated family conflicts. From a legal perspective, adaptive responses have emerged through judicial ijtihad, particularly in addressing contemporary issues such as the use of digital evidence in family law cases. However, strong resistance within formal legislation persists, resulting in a significant legal vacuum. These findings highlight the need for a more responsive reform of Islamic family law that engages with social and technological change while maintaining its normative foundations